Identification, characterisation and application of inducible gene expression systems in Cupriavidus necator H16 and other bacteria - Hanko, Erik K. R. (2020)
The production of key building block chemicals from renewable resources or waste forms a rapidly growing segment of the bioeconomy. The conversion of waste gases, such as carbon dioxide or carbon monoxide, into value-added compounds using metabolically engineered microorganisms has significant potential to maintain economic independence while reducing greenhouse gas emissions. Modification of cellular metabolism for the biosynthesis of a target molecule often requires an adjustment of gene expression, either of an endogenous or a heterologous metabolic pathway. Transcription factors are DNA-binding proteins that control gene expression at the transcriptional level in response to physical parameters, ions, or small effector molecules. They have become indispensable tools for the advancement of synthetic biology and metabolic engineering. In this work, significant progress was made in the discovery and characterisation of transcription factor-based inducible gene expression systems for metabolic engineering of the chemolithoautotroph Cupriavidus necator H16 and other bacteria. Firstly, a quantitative evaluation of a range of well characterised heterolougous inducible systems in C. necator was undertaken. Four of them, the positively regulated L-arabinose- and L-rhamnose-inducible systems and the negatively regulated acrylate- and cumate-inducible systems, were subsequently employed for the biosynthesis of the industrially relevant building block chemical isoprene. In addition to being used for controlling expression of structural genes, transcription factor-based inducible systems have gained increasing interest for their application as genetically encoded biosensors. Their ability to transduce the intracellular concentration of a target molecule into an output signal detectable in a high throughput format has the potential to revolutionise the field of microbial cell factory development. Currently, the number of compounds of biological interest by far exceeds the number of available biosensors. Here, this limitation was addressed by developing a universal genome-wide approach to identify novel transcription factor-based inducible gene expression systems. Once developed, the methodical pipeline was evaluated in the metabolically versatile C. necator. In total, 15 novel or little characterised inducible systems were identified and their broad host-range applicability was exemplified in three industrially relevant prokaryotes. Novel interactions between existing sensors and compounds of biological relevance were discovered by employing the largest reported library of transcription factor-based inducible systems in an automated high throughput screen. The same strategy, which was pursued in order to mine native inducible systems from the genome of C. necator, was used to source inducible systems responding to the industrially relevant platform chemicals 3-hydroxypropionic acid (3-HP) and itaconic acid. The HpdR/PhpdH-3-HP-inducible system from Pseudomonas putida KT2440 and the ItcR/Pccl-itaconic acid-inducible system from Yersinia pseudotuberculosis were thoroughly characterised for their regulator- and ligand dependent orthogonality, induction kinetics and dynamics. This thesis highlights their potential to be applied as biosensors for high-throughput microbial strain development to facilitate improved 3-HP and itaconate biosynthesis.